The Roles of FHL3 in Cancer - Huang, Zhenjun; Yu, Chengpeng; Yu, Liqing; Shu, Hongxin; Zhu, Xianhua (Frontiers in Oncology, 2022)
The four and a half LIM domain protein 3, also named the LIM-protein FHL3, belongs to the LIM-only family. Based on the special structure of LIM-only proteins, FHL3 can perform significant functions in muscle proliferation and cardiovascular diseases by regulating cell growth and signal transduction. In recent years, there has been increasing evidence of a relation between FHLs and tumor biology, since FHL3 is often overexpressed or downregulated in different cancers. On the one hand, FHL3 can function as a tumor suppressor and influence the expression of downstream genes. On the other hand, FHL3 can also play a role as an oncoprotein in some cancers to promote tumor progression via phosphorylation. Thus, FHL3 is proposed to have a dual effect on cancer progression, reflecting its complex roles in cancer. This review focuses on the roles of FHL3 in cancer progression and discusses the interaction of FHL3 with other proteins and transcription factors. Finally, the clinical significance of FHL3 for the treatment of cancers is discussed.